أثر الخدمات الإلكترونية على رضا العملاء في الدوائر الحكومية – دراسة حالة: دائرة الجمارك الأردنية - Abdullah Yousef Ibrahim Abu-Subha; Dojanah "Mohammed Qadri" Bader (International Journal of Computers and Informatics, 2024)
This study mainly aims to identify the impact of e-services provided by public sector departments on customer satisfaction and the level of service provided to them. Jordanian Customs was adopted as a case study in which some computerized systems are used in the procedures of dealing with customers, such as:  e-Public Service System, ASYCUDA Global System Service, Customs Tariff Application Service via cellular devices, ATA admission e-service, and e-tracking service. To achieve this goal, a questionnaire was designed containing 46 paragraphs related to the variables of the study, divided into: (32) paragraphs measuring the dimensions of e-services, and (14) paragraphs measuring customer satisfaction,  The researchers in this study used descriptive, analytical, and field survey approaches, and the study reached a set of results centered on the existence of a statistically significant impact of the e-services provided by Jordan Customs and the existing application systems on customer satisfaction. In light of the results, the current study recommends the following:                                                    1. Generalize the results of the study to the decision makers in Jordan Customs to identify strengths and weaknesses, and embody the principle of research and development in the department.2. Developing the e-public service and creating a mechanism that helps clients accomplish their transactions in one place instead of moving between the directorates of the department's main offices or between the customs centers and the department.3. The need to provide a strong network, software, and programs that support the global ASYCUDA system to prevent frequent disconnections and develop a mechanism or a system that saves data first in the event of disconnection.4. Reconsidering the ATA admission e-service by a specialized committee of programmers with the aim of modernizing and developing it so that it is easier to use in order to enhance usability.
Keywords: Electronic Service; Customer Satisfaction; Electronic Customer Service Unit; ASYCUDA System; Mobile CITS (Customs Integrated Tariff Services); Jordan Customs